Mineralización del carbono y nitrógeno y retención de humedad en suelos tratados con el alga Macrocystis pyrifera - Sarpi Ruiz, G.; ETCHEVERS, J.D. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Along the Chilean coast there are wide varieties of seadweeds, the Macrocystis genus being very abundant. Little or no research has been done concerning its use in agriculture or industry, although some farmers from southern Chile add the algae as soil ammendment to potato crop. The effect of three rates of Macrocystis pyrifera (20, 40 and 80 mg/100 g dried soil) on soil carbon and nitrogen mineralization ph and water holding capacity (WHC) was study for two Chilean soils, Trumao (Andepts) and Arenales (Psamments). The research was carried out at the school of Agronomy of the University of Concepcion, Chillan, Chile. Incubation of these soils with M. pyrifera meal, previously washed with fresh water, resulted first in a net immovilization of inorganic nitrogen followed by net nitrogen mineralization. At the end of the incubation period (107 days), the concentration of inorganic nitrogen was significantly higher in the soils containing algae. This increase was more evident in the Trumao soil, where a positive "priming effect" was obtained. In the Arenales soil a negative "priming effect" resulted from the addition of algae. In both soils, CO2 evolution, when compared to the check, showed that only the 80 mg of algae/100 g soil doses promoted a significant increase in CO2 production. In the Trumao soil this treatment resulted in a positive "priming effect", that is, it accelerated the native organic matter mineralization, thus altering its stability. In the Arenales soil the algae addition resulted in a negative "priming effect", as measured by CO2 evolution. Addition of algae in all doses increased the water holding capacity (WHC) in both soils, being this affect more evident in the Arenales. The addition of the algae decreased the Trumao soil pH and increased the Arenales soil pH. This effect was more evident as the incubation time went on, especially at the highest levels of algae.